Vertical distributions and abundances of life stages of the euphausiid Euphausia pacifica in relation to oxygen and temperature in a seasonally hypoxic fjord. (25th March 2019) - Li, Lingbo; Keister, Julie E; Essington, Timothy E; Newton, Jan
Abstract: It is broadly assumed that organisms inhabiting seasonally hypoxic estuaries and fjords are stressed by low dissolved oxygen (DO) conditions. However, relatively few zooplankton have shown clear avoidance of hypoxic water except when oxygen was extremely low. We investigated vertical distributions and abundance of the euphausiid Euphausia pacifica in the seasonally hypoxic Hood Canal, Washington using depth-stratified zooplankton net tows and CTD casts, monthly from June to October in 2012 and 2013 at two sites that contrasted in oxygen conditions. We separated E. pacifica into five life stages based on their ontogenetic development and swimming ability and related their density (#/m 3 ) within each depth layer to the corresponding environmental variables using delta Generalized Linear Mixed Models (GLMMs). The models detected strong seasonal and spatial differences with no additional significant effects of DO or temperature. GLMMs showed that whole water-column abundances of calyptopes and furcilia I–III stages were more strongly related to DO and temperature than other stages. Overall, only modest effects of DO were observed, possibly because of the low temperatures and moderate DO levels compared to recent years. Combined laboratory experiments and multi-year mooring data show that conditions in other years could have resulted in direct mortality.